Substitution of polysorbates by plant-based emulsifiers: impact on vitamin D bioavailability and gut health in mice - Ángela Bravo-Núñez; Angélique Berthomé; Charlotte Sabran; Donato Vairo; Jean-Charles Martin; Katherine Alvarado-Ramos; Benoit Chassaing; Julie Tomas; Emmanuelle Reboul (Communications Biology)
Abstract Although long considered safe, recent data have shown that emulsifiers such as polysorbates promoted intestinal inflammation and were associated with increased risks of developing chronic pathologies. We evaluated the potential of plant-based emulsifiers (pea protein isolate, PPI, and corn arabinoxylans, CAX) as alternatives to Polysorbate 80 (Tween 80, T80). Combining PPI and CAX led to a similar vitamin D3 bioavailability to T80 in vitro and in vivo in mice. We then exposed female and male mice to dietary doses of emulsifiers in oil-in-water emulsions (180 mg/kg/day for T80, 5 days/week) for 11 weeks. Conversely to previous studies conducted with higher doses of emulsifiers, T80, PPI, and PPI + CAX groups were similar to the control group (oil alone) in terms of physiological characteristics and inflammation biomarkers. However, LPS-specific serum IgG levels were reduced in the PPI (−31.05%, p = 0.0006) and PPI + CAX (−34.66%, p = 0.0001) groups compared to the T80 group at the end of the intervention. Exposure to T80, but not to PPI or PPI + CAX, reduced the distance between bacteria and the jejunal epithelium (−60.67%, p = 0.0779) and significantly increased Firmicutes_D phylla in male mice. Overall, we showed that a combination of pea protein and arabinoxylans appears as a sustainable alternative to polysorbates for vitamin D3 delivery.